Contributions of wild and provisioned foods to the diets of domestic cats that depredate wild animals. Issue 9 (26th September 2021) - Cecchetti, Martina; Crowley, Sarah L.; Goodwin, Cecily E. D.; Cole, Holly; McDonald, Jennifer; Bearhop, Stuart; McDonald, Robbie A.
Abstract: Predation of wildlife by domestic cats Felis catus presents a threat to biodiversity conservation in some ecological contexts. The proportions of wild prey captured and eaten by domestic cats and thus the contributions of wild prey to cat diets are hard to quantify. This limits the understanding of any impacts of cats may have on wild animal populations and confounds analyses of the effects of interventions aimed at reducing wildlife killing. We used stable isotope analyses to quantify the relative contributions of wild and provisioned foods to the diets of domestic cats kept as companion animals and which frequently captured wild prey. We tested the effects of treatments aimed at reducing killing upon stable isotope ratios of cat whiskers and, where treatments had significant effects, we estimated variation in the contributions of wild prey to cats' diets before and during treatment. We evaluated bells, Birdsbesafe collar covers, provision of food in a "puzzle feeder, " provision of food in which meat was the principal source of protein, object play, and a control group. As expected, cat diets consisted primarily of provisioned foods, though the contribution of wild animals to the diets of these cats, all of which regularly caught wild animals, was low (cat food ˜96%, wild animals ˜3–4%). Compared to the pre‐treatment period and control group, cats with a Birdsbesafe collar cover exhibited a significant reduction in nitrogen stable isotope ratios in their whiskers and consumed less wild prey, most likely attributable to effective inhibition of hunting, particularly for birds. Fitting cats with a Birdsbesafe collar cover, therefore, reduced both returns of wild birds and consumption of wild prey. While multiple interventions can significantly affect the numbers of wild animals that cats capture and return home, the remarkably small dietary contributions made by wild animal prey mean dietary change is harder to discern. Domestic cats rely almost exclusively on food provided by people, even when they frequently kill wild animals. This suggests that the hunting behavior of domestic cats may be driven by behavioral motivations, or by a need to address micronutrient requirements, but is unlikely to alter macronutrient intake.